ChemInform Abstract: Progressive Macromolecular Self‐Assembly: From Biomimetic Chemistry to Bio‐Inspired Materials. Issue 48 (26th November 2013) - Zhao, Yu; Sakai, Fuji; Su, Lu; Liu, Yijiang; Wei, Kongchang; Chen, Guosong; Jiang, Ming
Abstract Review: 219 refs.